Intimate partner violence and eating behavior of adult women: narrative synthesis of recent evidence (Brazilian Journal of Health Research, 2025)
Introduction: Intimate partner violence (IPV) is a major public health issue that disproportionately affects women and is associated with multiple negative outcomes for physical and mental health. Objective: To conduct a narrative review of the scientific literature on the relationship between IPV and eating behavior in adult women. Methods: Searches were conducted in the PubMed, SciELO, and LILACS databases for studies published between 2015 and 2025. Results: Of the 30 articles identified, five met the inclusion criteria. The findings reveal that IPV is associated with significant changes in eating behavior, such as binge eating, loss of appetite, emotional eating, retaliatory eating, and the development of eating disorders, often mediated by psychological mechanisms. Conclusion: The scarcity of studies on the subject highlights the need for further scientific investigation and for an interdisciplinary approach by health professionals in identifying and sensitively managing these issues.
Keywords: Intimate partner violence; Violence against women; Eating behavior; Disordered eating behavior